The gentrification of a post-industrial English rural village: Querying urban planetary perspectives - Phillips, Martin Peter (2022)
Recent years have seen the growth of planetary perspectives related to urbanisation and gentrification that havechallenged the significance of differentiations of rural and urban space. This paper explores the argumentsadvanced in these perspectives, highlighting claims that they are based on a critique of methodological terri-torialism that has long been employed in rural and urban studies, as well as exhibiting an urbanormativity thatwas arguably absent from some earlier critiques of people such as Ray Pahl. This paper seeks to develop a studyof rural gentrification that avoids urbanormativity and methodological territorialism. After reviewing debatesrelated to academic and lay conceptions of the urban and rural, the paper highlights how territorial represen-tations may warrant investigation even when social practices may be seen to routinely traverse boundaries of, forexample, the rural. The relevance of these ideas to gentrification is then explored through an investigation of thegentrification of a village, which like many ‘urban’ settlements, has experienced both industrialisation and de-industrialisation. Drawing on the results of a ‘mixed-method questionnaire’ conducted in this village in Cal-derdale, England, the paper explores how the lives of residents are connected into more and less distant urbanspaces through an analysis of migrational movements and employment relations, including commuting patterns.It is argued that, in line with arguments advanced within studies of planetary urbanisation/gentrification, thereis considerable interconnection between the village and areas that have been classified as urban. However, it isalso shown that neither this interconnection, nor the areas industrial past, means that symbolic and affectivesenses of rurality are insignificant to village residents, or to the practices of gentrification that have emerged.This did not mean that representations of rurality were unimpacted by industry and urban connectivity, with thepaper detailing that whilst the village was widely seen as rural, it was also often seen as exhibiting significantunconformity from expectations of rurality. The paper ends by considering how senses of separation and con-nectivity to urban and industrial spaces link to different types of gentrifiers colonising the village.